Transmissão das infecções sexualmente transmissíveis – ISTs - entre adolescentes: uma proposta de abordagem metodológica investigativa pela produção de vídeos - Vanessa Rodrigues Viana Medeiros (2020)
The incidence of Sexually Transmitted Infections – STIs - is a national and global public health problem; it currently shows an upward trend among young people and adoles-cents in Brazil. Through information that advocates enhancing the sexual and reproductive health of this population, this work presents an analysis of four audiovisual productions and answers a questionnaire of previous knowledge, applied to high school students. Additionally, an investigative teaching sequence (ITS) is proposed, all on the STI theme. That ITS proposes as stages of an audiovisual production about STI in high school, being initiated by a questionnaire of previous knowledge. Three of the four audiovisual productions analyzed were found on Youtube. Only one was produced by students from the same school where the questionnaire was applied as a result of the start of application of ITS, but adapted to basic education. The main requirement for the selection of the videos analyzed in this work was that they all presented the methodological didactic criteria determined by the ITS, in addition to not showing the student´s faces. The results obtained demonstrated, in general, sufficient quality of audiovisual productions, both of the techniques used and of the way in which the content was worked, showing a real possibility of success in a future application of ITS to high school students. Finally, it is concluded that the application of audiovisual productions as an ITS, guided by answers to a questionnaire of previous knowledge, is an efficient methodological strategy in the prevention of STIs because it stimulates the search for knowledge of these diseases and their way of prevention, positively modifying sexual behavior of students.